Long-term zinc treatment alters the mechanical properties and metabolism of prostate cancer cells - Navratil, Jiri; Kratochvilova, Monika; Raudenska, Martina; Balvan, Jan; Vicar, Tomas; Petrlakova, Katerina; Suzuki, Kanako; Jadrna, Lucie; Bursa, Jiri; Kräter, Martin; Kim, Kyoohyun; Masarik, Michal; et al. (Cancer cell international, 2024)
The failure of intracellular zinc accumulation is a key process in prostate carcinogenesis. Although prostate cancer cells can accumulate zinc after long-term exposure, chronic zinc oversupply may accelerate prostate carcinogenesis or chemoresistance. Because cancer progression is associated with energetically demanding cytoskeletal rearrangements, we investigated the effect of long-term zinc presence on biophysical parameters, ATP production, and EMT characteristics of two prostate cancer cell lines (PC-3, 22Rv1). Prolonged exposure to zinc increased ATP production, spare respiratory capacity, and induced a response in PC-3 cells, characterized by remodeling of vimentin and a shift of cell dry mass density and caveolin-1 to the perinuclear region. This zinc-induced remodeling correlated with a greater tendency to maintain actin architecture despite inhibition of actin polymerization by cytochalasin. Zinc partially restored epithelial characteristics in PC-3 cells by decreasing vimentin expression and increasing E-cadherin. Nevertheless, the expression of E-cadherin remained lower than that observed in predominantly oxidative, low-invasive 22Rv1 cells. Following long-term zinc exposure, we observed an increase in cell stiffness associated with an increased refractive index in the perinuclear region and an increased mitochondrial content. The findings of the computational simulations indicate that the mechanical response cannot be attributed exclusively to alterations in cytoskeletal composition. This observation suggests the potential involvement of an additional, as yet unidentified, mechanical contributor. These findings indicate that long-term zinc exposure alters a group of cellular parameters towards an invasive phenotype, including an increase in mitochondrial number, ATP production, and cytochalasin resistance. Ultimately, these alterations are manifested in the biomechanical properties of the cells.
Keywords: Cancer; Actin; Mechanobiology; Metabolism; Mitochondria; Cytoskeleton; Zinc; Vimentin